Pertimbangan Hakim Dalam Menjatuhkan Putusan Pidana Atas Tindak Pidana Peredaran Uang Palsu (Studi Kasus Nomor 347/Pid.B/2021/PN Smg) - Indra Prasetya; Arista Candra Irawati (ADIL Indonesia Journal, 2024)
The judge's considerations in imposing a criminal decision on the crime of circulation of counterfeit money (Case Study Number 347/Pid.B/2021/PN Smg) The crime of circulation of counterfeit money is regulated in Law Number 7 of 2011 concerning currency and regulated in Article 244 of the Criminal Code concerning Counterfeiting of currency and paper money, and regulated in Law Number 10 of 1998 concerning Amendments to Law Number 7 of 1992 concerning Banking, money as legal means of payment and illegal money is referred to as counterfeit money. The criminal act of circulating counterfeit money as referred to in the Laws and Regulations so that the judge's sentencing decision gives and imposes on mitigating circumstances and aggravating circumstances for the defendant. This study aims to find out the judge's considerations in imposing criminal decisions on the circulation of counterfeit money and how to convict the circulation of counterfeit money. This study uses a juridical-empirical approach using interview data with Class 1A Semarang District Court judges. The results obtained by the research show that the judge's consideration underlies the existence of an unlawful act to lead to a judge's decision. It can be concluded that: the judge's consideration certainly underlies the facts of the trial after carrying out the trial agenda to be used as the basis for the judge's assessment to give a decision, the judge will assess the facts of the trial with valid evidence that can be accounted for by the Public Prosecutor and the defendant so that the judge gives a decision that is contains certainty, fairness, benefits for all parties. Abstrak Pertimbangan hakim dalam menjatuhkan putusan pidana atas Tindak Pidana Peredaran Uang Palsu(Studi Kasus Nomor 347/Pid.B/2021/PN Smg) Tindak Pidana peredaran uang palsu diatur dalam Undang-Undang Nomor 7 Tahun 2011 tentang mata uang dan di atur dalam Pasal 244 KUHP tentang Pemalsusan mata uang dan uang kertas, dan di atur dalam Uandang-UndangNomor 10 Tahun 1998 tentang Perubahan atas Undang-Undang Nomor 7 Tahun 1992 tentang Perbankan,uang sebagai alat pembayaran yang sah dan uang tidak sah sebagaimana dimaksud sebagai uang palsu. Tindak Pidana peredaran uang palsu sebagaimana dimaksud dalam Peraturan Perundang-Undangan sehingga Putusan Pemidanaan hakim yang memberikan dan menjatuhkan atas keadaan yang meringankan dan keadaan yang memberatkan terdakwa.Penelitian ini bertujuan untuk mengetahui pertimbangan hakim dalam menjatuhkan putusan pidana Peredaran uang palsu danbagaimana penjatuhan pidana peredaran uang palsu,Penelitian ini menggunakan metode pendekatan Yuridis-empiris dengan menggunakan data wawancara kepada HakimPengadilan Negeri Semarang Kelas 1A.Hasil di peroleh penelitian menunjukkan pertimbangan hakim mendasari adanya perbuatan melawan hukum untuk menuju amar keputusan hakim. diperoleh kesimpulan bahwa:pertimbangan hakim tentunya mendasari fakta persidangan setelah melakukan agenda persidangan untuk dijadikan dasar penilaian hakim untuk memberikan keputusan, hakim akan menilai dari fakta-fakta persidangan dengan alat bukti sah yang dapat di pertanggungjawabkan dari Jaksa Penuntut Umum maupun terdakwa sehingga hakim memberikan keputusan yang mengandung kepastian, keadilan, kemanfaatan bagi semua pihak.